Development of User-Centered Smart Child Seat for NCAP Requirements Via IoT Platform - Azmi, Nur Fatihah; Arith, Faiz; Mokhtar, Nur Hazwani; Norman, Mohamad Faiz (Wydawnictwo SIGMA-NOT, 2021)
Recently, the 'forgotten baby syndrome' term has become a regular headline in the newspaper. The syndrome is referred to a scenario of a child dying from a heat stroke after being accidentally left in a car. Herein, the Smart Child Seat (SCS) has been designed with a real-time monitoring-based system that consists of temperature, humidity, heart rate, sound, ultrasonic and a carbon monoxide sensor to monitor and measure the condition of the child left inside the car. The system's requirement is designed based on the market survey to provide direction for the optimized SCS system. The system will send the notification via the Blynk IoT application to the parents if there is an abnormal reading from the sensors